Employees’ satisfaction between 1996 and 2008 within the Portuguese financial sector - Santos, S. C. (2011)
This research includes two complementary studies. Study 1 intends to analyze the stability of the latent construct job satisfaction over time, through four facets - satisfaction with relationships, rewards, human resources management practices and work itself. Study 2 aims to compare the results obtained with an aggregate weighted measure of job satisfaction (Aggregated Job Satisfaction) and a single item measure (Overall Job Satisfaction). Both are cross-sectional studies with repeated measures on six time moments over a twelve years period (1996-2008) in the Portuguese financial sector organizations. Results from study 1 evidences the structural invariance of the latent construct job satisfaction and the different loading pattern on each facet, over time. Study 2 evidences that the overall job satisfaction and the aggregated job satisfaction measures displays a similar pattern of results overtime. Moreover, job satisfaction facets predicts overall job satisfaction. Theoretically, this research presents a wider view on job satisfaction issues: its facets, the debate on aggregated vs overall measures and relationships patterns over time. Moreover, satisfaction with human resources management emerges as the stronger predictor of overall job satisfaction in all the six time periods. Results suggest that managers can improve satisfaction through performance appraisal systems and training.